Ulva blooms in the southwestern Gulf of California: Reproduction and biomass. (5th January 2018) - Chávez-Sánchez, Tonatiuh; Piñón-Gimate, Alejandra; Serviere-Zaragoza, Elisa; López-Bautista, Juan Manuel; Casas-Valdez, Margarita
Abstract: Ulvacean blooms are generally characterized by one or more Ulva species, some of which are common to blooms across a broad geographic range. In tropical environments the identified stimuli that induce reproductive development of Ulva are restricted to temperature, salinity, dehydration and fragmentation. Culture studies have been prolific in describing the reproduction of Ulva species, but its reproductive changes in natural environment have not been described yet. Hence, seasonal changes were described in reproductive stages and their relationship with biomass and environmental factors of Ulva species at four macroalgal blooms in a subtropical bay. Eight Ulva species were found: U. acanthophora, U. clathrata, U. flexuosa, U. intestinalis, U. lactuca, U. lobata, U. nematoidea and U. rigida. Reproductive stage and biomass varied according to site and season. Five species showed four reproductive stages (vegetative, thallus with fully differentiated zooids in formation and empty cells after zooids release); for the remaining species only vegetative thalli were found. Ulva rigida showed the highest biomass values, followed by U. acanthophora, following a seasonal pattern.